Occurrence and analysis of factors related dystocia cows in Agreste Meridional Pernambuco - Filho, Alonso Pereira Silva; Costa, Nivaldo de Azevedo; Carneiro, Gustavo Ferrer; Souto, Rodolfo José Cavalcanti; Mendonça, Carla Lopes; Afonso, José Augusto Bastos (Brazilian Journal of Veterinary Medicine, 2014)
ABSTRACT. Silva Filho A.P., Costa N.A., Carneiro G.F., Souto R.J.C., Mendonça C.L. & Afonso J.A.B. [Occurrence and analysis of factors related dystocia cows in Agreste Meridional Pernambuco.] Ocorrência e análise de fatores relacionados à distocias em vacas no Agreste Meridional de Pernambuco. Revista Brasileira de Medicina Veterinária, 36(3):317-321, 2014. Clínica de Bovinos, Universidade Federal Rural de Pernambuco, Avenida Bom Pastor, s/n, Campus de Garanhuns, Boa Vista, PE 55292-270, Brasil. E-mail: alonsopsfilho@yahoo.com.br The technification creations and introduction of new more specialized breeds are improving the productivity indices of the herds, however is associated with increased incidence of dystocia. This aimed to describe the main factors related to the occurrence of laborious births in cows treated in hospital routine. In this study, information was retrieved from clinical records of cows (n = 837), with situations of dystocia (maternal and / or fetal), between the period 2000 to 2010. This disease accounted for 17.5% (837/4782) of the sample from cattle treated at the Clinic for Cattle Garanhuns Federal Rural University of Pernambuco. One of the important findings was the previous manipulation in the properties by unqualified persons representing high risk of life for calves (60% death) and cows (15% death). The occurrence of this disease in primiparous cows (2-3 years) was 34.2% in pluriparous (4-6 years) were 44.2%, and the cows over the age of six years were 21.6%. This type of reproductive disorder causes great economic losses, mainly due to the high mortality of fetuses and pregnant women and is associated mainly to delays in care and previous manipulation in the property by persons not trained.